2023
DOI: 10.3390/polym15122665
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Thermal Degradation of an Acrylamide and 2-Acrylamido-2-Methylpropanesulfonic Acid Copolymer at High Temperatures

Abstract: As a temperature-resistant and salt-resistant polymer, acrylamide and 2-acrylamide-2-methylpropane sulfonic acid (abbreviated as AM-AMPS) copolymer is currently widely used in drilling, water control and oil production stabilization, enhanced oil recovery and other fields, but its stability under high temperature has been less studied. The degradation process of the AM-AMPS copolymer solution was studied by measuring viscosity, the degree of hydrolysis, and weight-average molecular weight at different temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…It can be found that the apparent viscosity of AA/AM/AOS/C 16 ‐DMAAC increased firstly with the increasing concentration of NaCl, reaching the maximum (about 350 mPa·s) at 2000 mg/L of NaCl, then gradually decreased with the increment of mineralization degree. Specifically, at low salinity degree, the hydrophobic association of AA/AM/AOS/C 16 ‐DMAAC was enhanced by the influence of salt ions, improving the apparent viscosity of AA/AM/AOS/C 16 ‐DMAAC 27,29,30 . While the anti‐polyelectrolyte effect of AA/AM/AOS/C 16 ‐DMAAC was significant after concentration of NaCl exceeding 2000 mg/L.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It can be found that the apparent viscosity of AA/AM/AOS/C 16 ‐DMAAC increased firstly with the increasing concentration of NaCl, reaching the maximum (about 350 mPa·s) at 2000 mg/L of NaCl, then gradually decreased with the increment of mineralization degree. Specifically, at low salinity degree, the hydrophobic association of AA/AM/AOS/C 16 ‐DMAAC was enhanced by the influence of salt ions, improving the apparent viscosity of AA/AM/AOS/C 16 ‐DMAAC 27,29,30 . While the anti‐polyelectrolyte effect of AA/AM/AOS/C 16 ‐DMAAC was significant after concentration of NaCl exceeding 2000 mg/L.…”
Section: Resultsmentioning
confidence: 95%
“…Especially, from 30 °C to 70 °C, apparent viscosity of AA/AM/AOS/C 16 ‐DMAAC decreased from 364 to 294 mPa·s, while the apparent viscosity of HPAM decreased from 188 to 104 mPa·s. In addition, the temperature‐resistance of AA/AM/AOS/C 16 ‐DMAAC (with a viscosity retention rate of 77.94%) was better than that of HPAM (with a viscosity retention rate of 55.26%) at 70 °C, which can be attributed to introduction of sulfonic acid groups into AA/AM/AOS/C 16 ‐DMAAC for inhibiting it hydrolysis at high temperatures 26,27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation